Ruminal degradability of forage and crop residues in Brown Swiss cattle - Contreras P., José L. (2019)
The aim of this study was to determine the degradability of the association of forages and crop residues commonly used to feed cattle in the Huancavelica Region. The forage associations were white clover-Italian ryegrass and red clover-dactylis, while the harvest residues were maize, oat straw, peas, beans and quinoa. For the determination of the degradability of dry matter (DM), crude protein (CP) and neutral detergent fibre (NDF), three rumen fistulated Brown Swiss cattle were used. Samples of forages and harvest residues were placed in nylon bags and incubated for 4, 8, 12, 24, 48, 72 and 96 hours. Time zero (t0) was used for the calculation of the soluble fraction. The DM, CP and NDF degradability were influenced by forages and crop residues (p<0.05). The greater potential degradability of the DM and CP, and effective degradability of the DM, CP and NDF give the white clover-Italian ryegrass a good nutritional potential for ruminants. The constant rate (C) of degradation, potential degradability and effective degradability of the CP allows to consider the residues of peas, beans and quinoa as food resources of high nutritional quality. On the contrary, the effective degradability of the PC at the passage rate of 5%/h indicates that maize and oat straw are medium quality foods.